2019
DOI: 10.3390/ijms21010105
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Novel cGAS Homologues Using a Combination of in Vitro and In Vivo Protein Synthesis

Abstract: The cyclic GMP-AMP synthase (cGAS) catalyzes the synthesis of the multifunctional second messenger, cGAMP, in metazoans. Although numerous cGAS homologues are predicted in protein databases, the catalytic activity towards cGAMP synthesis has been proven for only four of them. Therefore, we selected five novel and yet uncharacterized cGAS homologues, which cover a broad range in the field of vertebrates. Cell-free protein synthesis (CFPS) was used for a pre-screening to investigate if the cGAS genes originating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 44 publications
(68 reference statements)
1
43
0
Order By: Relevance
“…As shown in Table 2 , the reaction rate of 2′3′-cGAMP synthesis was the highest in the first experiment with a specific activity of 0.052 ± 0.014 U mg −1 , although higher thscGAS concentrations were used in the subsequent experiments. This value is in the typical range for the intrinsic specific activity of thscGAS, demonstrating that the thscGAS-catalyzed reaction was running close to its optimum in these enzyme cascade conditions [ 25 ]. The specific thscGAS activity with changed enzyme ratios (50:5:50:120) was only 0.012 ± 0.004 U mg −1 , which indicates that not enough ATP was provided by the cascade to fully exploit the activity of thscGAS.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…As shown in Table 2 , the reaction rate of 2′3′-cGAMP synthesis was the highest in the first experiment with a specific activity of 0.052 ± 0.014 U mg −1 , although higher thscGAS concentrations were used in the subsequent experiments. This value is in the typical range for the intrinsic specific activity of thscGAS, demonstrating that the thscGAS-catalyzed reaction was running close to its optimum in these enzyme cascade conditions [ 25 ]. The specific thscGAS activity with changed enzyme ratios (50:5:50:120) was only 0.012 ± 0.004 U mg −1 , which indicates that not enough ATP was provided by the cascade to fully exploit the activity of thscGAS.…”
Section: Resultsmentioning
confidence: 96%
“…In order to provide sufficient amounts of intermediates for the subsequent reaction step, the synthesis of 2′3′-cGAMP was started after 35 min by adding thscGAS, 0.5 mM GTP as the second substrate and 0.1 mg mL −1 HT DNA, required for thscGAS activation. A thscGAS concentration of 40 mg L −1 was chosen, as this concentration was commonly used in previously established assays [ 24 , 25 ]. The results of the reaction progress of the first thscGAS coupled cascade experiment are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, specific activities of cGAS variants were determined using in vitro assay and RP-HPLC measurements of cGAMP production. Although, the zebrafish cGAS homologue has low amino acid identity to human cGAS (less than 35%), their similar activities were determined [ 179 ]. Liu and co-workers [ 160 ] reported that overexpression of zebrafish cGASa/b in HEK293T cells and zebrafish embryos significantly activated NF-κB and type I IFN signaling pathways in a STING-dependent manner, and that cGASa, but not cGASb, was involved in immunoglobulin Z-mediated mucosal immunity in gill-associated lymphoid tissue, suggesting differential functions between the two DrcGASs [ 160 ].…”
Section: Cgasmentioning
confidence: 99%